Valorization of a By-Product from the Production of Mechanically Deboned Chicken Meat for Preparation of Gelatins - Mokrejš, Pavel; Gál, Robert; Pavlačková, Jana; Janáčová, Dagmar (Molecules (Basel, Switzerland), 2021)
In recent decades, food waste management has become a key priority of industrial and food companies, state authorities and consumers as well. The paper describes the biotechnological processing of mechanically deboned chicken meat (MDCM) by-product, rich in collagen, into gelatins. A factorial design at two levels was used to study three selected process conditions (enzyme conditioning time, gelatin extraction temperature and gelatin extraction time). The efficiency of the technological process of valorization of MDCM by-product into gelatins was evaluated by % conversion of the by-product into gelatins and some qualitative parameters of gelatins (gel strength, viscosity and ash content). Under optimal processing conditions (48-72 h of enzyme conditioning time, 73-78 °C gelatin extraction temperature and 100-150 min gelatin extraction time), MDCM by-product can be processed with 30-32% efficiency into gelatins with a gel strength of 140 Bloom, a viscosity of 2.5 mPa.s and an ash content of 5.0% (which can be reduced by deionization using ion-exchange resins). MDCM is a promising food by-product for valorization into gelatins, which have potential applications in food-, pharmaceutical- and cosmetic fields. The presented technology contributes not only to food sustainability but also to the model of a circular economy.
Keywords: food sustainability; gelatin; food by-products; extraction; sustainability; Chickens; Temperature; viskozita; teplota; valorization; Bone and Bones; Viscosity; kosti a kostní tkáň; želatina; zvířata; Meat; mechanically deboned chicken meat (MDCM) by-product; Gels; circular economy; kur domácí; gely; Gelatin; maso; biotechnology; Animals